2021
DOI: 10.1182/blood.2020009280
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab discontinuation in children and adults with atypical hemolytic-uremic syndrome: a prospective multicenter study

Abstract: The optimal duration of eculizumab treatment in patients with atypical haemolytic uremic syndrome (aHUS) remains poorly defined. We conducted a prospective national multicentric open-label study in order to assess eculizumab discontinuation in children and adults with aHUS. Fifty-five patients (including 19 children) discontinued eculizumab (mean duration of treatment, 16.5 months). Twenty-eight (51%) patients had complement gene rare variants, mostly in MCP (n= 12, 22%), CFH (n= 6, 11%) and CFI (n=6, 10%) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 22 publications
0
102
0
10
Order By: Relevance
“…This strategy may benefit the access of eculizumab without resulting in an excessive cost to the public health system, especially in low-income countries. However, to date, the best strategy to definided eculizumab interruption was based on genetic analysis [ 25 , 34 ]. The cost-effectiveness of accessing eculizumab for kidney transplant patients should be based on genetic analysis, thus, it is necessary to include the genetic profile for patients with suspicion for aHUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy may benefit the access of eculizumab without resulting in an excessive cost to the public health system, especially in low-income countries. However, to date, the best strategy to definided eculizumab interruption was based on genetic analysis [ 25 , 34 ]. The cost-effectiveness of accessing eculizumab for kidney transplant patients should be based on genetic analysis, thus, it is necessary to include the genetic profile for patients with suspicion for aHUS.…”
Section: Discussionmentioning
confidence: 99%
“…In those classified at high to moderate risk according to KDIGO 2017 [ 1 ] we strongly consider prophylaxis. As the opposite, we consider discontinuing the use in those without identified genetic variants, as well as the saving of 32 million euros realized by the STOPECU study [ 34 ] after the discontinuation of 55 patients with an average of 24 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with no complement gene variants, the risk of aHUS relapse was less than 5% but was significantly higher in carriers of complement gene variants reaching 50%. Time to relapse ranged from 1 to 22 months and was primarily precipitated by infections [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low relapse rates may be related to the low complement factor H mutations in the patient cohorts [6]. Fakhouri et al reported in their prospective study that discontinuation of eculizumab is reasonable and safe, in accordance with the complement mutation results of the patients [7]. The presence of complement gene abnormalities is a risk for aHUS relapse after anti-C5 treatment discontinuation, including in P-aHUS patients.…”
Section: Letter To the Editormentioning
confidence: 95%